Peripheral Neuropathy in Patients with Acute Leukemia Treated with Vincristine - Taslim E. Soetomenggolo (Indonesian Pediatric Society Publishing House, 2018)
Between December 1993 and December 1994, 46 patients with acute leukemia treated with vincristine were evaluated for the possibilities of peripheral neuropathy. Of the 46 patients, 39 patients had acute lymphoblastic leukemia, and 7 had acute non-lymphoblastic leukemia. All patients had received vincristine; 29 (63%) of the 46 patients had it for 5 - 9 weeks, and 17 (37%) had it for 4 weeks or less. rn 10 (21.7%) patients peripheral neuropathy was detected clinically, and in 35 patients (76%) the neuropathy was detected by electrodiagnostic examination. No evidence of neuropathy was detected in 11 patients. The electrodiagnostic examination was more sensitive than the clinical examination. Pe1ipheral neuropathy, either detected clinically or by means of electromyography, occurred mostly in patients with the dosage of vincristine of 5-20 mg, and the duration of treatment of 5-9 weeks.